ANALISIS EFISIENSI DAN EFEKTIVITAS PEMANFAATAN DANA BELANJA DAERAH DI UPT BALAI LATIHAN KERJA DELI SERDANG - Fitri Yani Panggabean; Oktarini Khamilah Siregar; Abdul Aziz Suendar Nasution (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
This study aims to determine how much the level of expenditure and the level of efficiency used by Deli Serdang Technical Implementation Unit in 2015-2017. The research method uses descriptive research. The type of data used is qualitative data. The data source of this research is the target and the realization of APBN funds in the year 2015-2017 obtained from the Deli Serdang Technical Training Center. This study uses descriptive data analysis techniques that begin by collecting information through interviews, data reduction, data presentation and at the end of making by concluding. The place of research was carried out at the Deli Serdang Technical Training Center. The study period starts from January 2019 until completion. The data of this study are secondary data. The analysis shows the level of efficiency seen in 2015 that is 86.57% and in 2016 decreased by 88.69% then in 2017 decreased by 89.25% seen from the percentage level shows the criteria are quite efficient by increasing the percentage level shows increasingly efficient. And the level of importance shows that it has been effectively seen in 2015 by 97.22% and in 2016 decreased by 93.50% then in 2017 it increased by 97.31% seen from the percentage level indicating the effective criteria. Because the greater the percentage shows more effective.